Follicular GH and IGF1 Levels Are Associated With Oocyte Cohort Quality: A Pilot Study - Scheffler, Florence; Vandecandelaere, Albane; Soyez, Marion; Bosquet, Dorian; Lefranc, Elodie; Copin, Henri; Devaux, Aviva; Benkhalifa, Moncef; Cabry, Rosalie; Desailloud, Rachel (Frontiers in Endocrinology, 2021)
Introduction Oocyte quality contributes to the development of an optimal embryo and thus a successful pregnancy. The objective of this study was to analyse the association between oocyte cohort quality and the follicular levels of growth hormone (GH), insulin-like growth factor 1 (IGF1), 25-hydroxy vitamin D (25OHD), thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4) and antithyroid antibodies, as a function of intracytoplasmic sperm injection (ICSI) outcomes. Material and methods We conducted a prospective comparative pilot study from January 2013 to December 2017. 59 ICSI cycles constituted an abnormal oocyte cohort (n=34 cycles, in which more than 50% of oocytes presented at least one morphological abnormality) and a normal oocyte cohort (n=25 cycles, in which 50% or less of the oocytes presented at least one morphological abnormality). GH, IGF1, 25OHD, TSH, fT3, fT4 and antithyroid antibodies were measured in follicular fluid. Results The fertilisation rate was lower in the abnormal oocyte cohort (65.5% vs. 80%, respectively, p=0.012). Oocytes’ proportion with at least one abnormality was 79.4% in the abnormal oocyte cohort and 29.0% in the normal oocyte cohort. The mean number of morphological abnormalities per oocyte was significantly higher in the abnormal oocyte cohort. The follicular levels of GH (4.98 vs. 2.75 mIU/L, respectively; p <0.01) and IGF1 (72.1 vs. 54.2 ng/mL, respectively; p=0.05) were higher in the normal oocyte cohort. There was no association with follicular levels of TSH, fT3, fT4, antithyroid antibodies, or 25OHD. Conclusion Oocyte cohort quality appears to be associated with follicular levels of GH and IGF1.